Proportionality Test in the 1945 Constitution: Limiting Hizbut Tahrir Freedom of Assembly - Taufik, Giri Ahmad (The Constitutional Court of the Republic of Indonesia, 2018)
In May 2017, Jokowiâs administration announced the intention to dissolve Hizbut Tahrir Indonesia (HTI). HTI is an Islamic organization that aspires to establish caliphate government based on the claim of Islamic teaching. The Government considers HTI as a threat to Pancasila. The announcement has created controversy. It has divided Indonesian into pro and contra camp. The dissolution pro camp argues HTI ideology is against Pancasila, Indonesia political ideology. Furthermore, they pointed out HTIâs idea of Caliphate that based on religion would disintegrate the nation. Conversely, the cons argues the government move is against the constitutionally guarantee freedom of association as stipulates in the 1945 Constitution of the Republic of Indonesia (hereafter the 1945 Constitution). The move would create precedent that threatens freedom of assembly if the government failed to enact due process procedure and provide justifiable reason for the action. This controversy is not new to human rights and democratic discourse. Karl Popper describes the debate as a paradox of tolerance, democracy, and freedom in an open society. This paper examines how the 1945 Constitution can be utilized to resolve the paradox. This paper argues that Article 28 J par.2 of the 1945 Constitution requires the balance between human rights protection and limitation in its proportion. Thus, the limitation clause should be used as a parameter to solve HTI issue. This paper explores the use of proportionality test in interpreting the limitation clause and applies it not only to the question of HTI issue but also broader issues to evaluate recent government moves in amending the Law Number 17 Year 2013 on Societal Organisation. This paper employs a doctrinal method in its analysis.